Application of Islamic architecture at Sultan Abdul Samad Building, Kuala Lumpur - Ismail, Sumarni; Nangkula, Utaberta; Mohd Yunus, Mohd.Yazid; Ismail, Nor Atiah (American-Eurasian Network for Scientific Information, 2015)
This paper discusses the analysis on the architecture of Sultan Abdul Samad (SAM) building in Kuala Lumpur. Specifically it will look at application of Islamic Architecture elements on the building. SAM was built during under British colonization. Designing the existing building took into consideration some of the features of buildings in several Islamic countries. The predominantly Moorish appearance of the building suitably reflects the cultural background of Malaysia. SAM is one of Malaysian Heritage list. It is important to revisit the principles behind it. What are the significant to local culture and how it being accepted towards Malay community.